SBP Is Superior to MAP to Reflect Tissue Perfusion and Hemodynamic Abnormality Perioperatively - Sun, Jie; Yuan, Jing; Li, Bin (Frontiers in Physiology, 2021)
Many articles reported intraoperative low mean artery pressure (MAP) or low systolic blood pressure (SBP) had an impact on organs function and patient outcome perioperatively. But which type of blood pressure should be paid more attention to is to be clarified. In our paper, we compared the impacting factors of MAP and SBP, used mathematical formula, arterial pulse contour calculation, and cardiovascular physiological knowledge to discuss which blood pressure was more able to reflect tissue perfusion and hemodynamic abnormality perioperatively. We conclude that MAP can reflect cardiac output change sensitively and SBP can reflect stroke volume change sensitively. Moreover, SBP can reflect the early hemodynamic changes, organs perfusion and heart systolic function. Compared with MAP, perioperative monitoring of SBP and timely detection and treatment of abnormal SBP are very important for early detection of hemodynamic abnormalities.